Relationship Between Self Confidence and The Anxiety in Facing The Working World To The Upper Degree Students Majoring Of Sendratasik Padang State University - Irdam; Harri Kurniawan; Geri Tio Nerido (Universitas Muhammadiyah Banjarmasin, 2021)
The purpose of this study was to determine the relationship between self-confidence and anxiety in facing the world of work in the final year students who are currently taking a thesis at the Sendratasik Department, State University of Padang. The research method used in this research is the quantitative method. The study population numbered 111 people with a sample size of 83 people. The sampling technique in this study is the random sampling technique. Test the validity and reliability in this study using the Alpha Cronbach technique. The item difference index on the Confidence scale moves from rix = 0.304 to rix = 0.801 with a reliability coefficient of α = 0.912. While the item difference index on the Anxiety scale moves from rix = 0.320 to rix = 0.702 with a reliability coefficient of α = 0.912. The technique of collecting data in this study is a scale. Hypothesis testing uses Product Moment testing techniques. Based on the data analysis, the hypothesis was obtained using the analysis formula, which obtained a significant value on the Confidence scale of p = 0.255 with KSZ = 1.014 and anxiety of p = 0.088 with KSZ = 1.251. These results indicate that the p value> 0.05 means that the distribution is normally distributed. Based on the test with Product Moment obtained a significant value of 0.000 smaller than the probability value <0.01. Therefore, as the basis for the decision-making of the Product Moment test, it can be concluded that the hypothesis is accepted with a negative directional correlation, thus there is a relationship between self-confidence and anxiety in final level students who are taking thesis in Sendratasik Department, Padang State University.